2019
DOI: 10.1186/s12889-018-6360-2
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual hygiene management in rural schools of Zambia: a descriptive study of knowledge, experiences and challenges faced by schoolgirls

Abstract: IntroductionWhile in school, girls require an environment that is supportive of menstrual hygiene management (MHM) in order to ensure regular school attendance and participation. Little is known about schoolgirls access to and practice of MHM in rural Zambia. This study explores girls’ experiences of MHM in rural schools of Zambia from the perspectives of schoolgirls, schoolboys and community and school-based adults key to MHM for schoolgirls.MethodsIn July and August 2015, we conducted this qualitative explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(144 citation statements)
references
References 29 publications
12
115
0
Order By: Relevance
“…A non-trivial share of the girls (13%) report having experienced period teasing, and fear of period teasing is almost universal (over 80%). The majority of previous qualitative studies that survey girls portray teasing as a common phenomenon and a major source of anxiety for girls [ 3 , 5 ]—we confirm this finding. The only other quantitative study to date, which was a non-representative poll of 1,000 U.K. girls aged 14-21, revealed that one in five girls have experienced teasing or bullying surrounding their periods [ 37 ].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…A non-trivial share of the girls (13%) report having experienced period teasing, and fear of period teasing is almost universal (over 80%). The majority of previous qualitative studies that survey girls portray teasing as a common phenomenon and a major source of anxiety for girls [ 3 , 5 ]—we confirm this finding. The only other quantitative study to date, which was a non-representative poll of 1,000 U.K. girls aged 14-21, revealed that one in five girls have experienced teasing or bullying surrounding their periods [ 37 ].…”
Section: Discussionsupporting
confidence: 83%
“…In recent years, an abundance of research and publicity has identified menstruation as an obstacle to gender equality in education, health, and work, particularly in low and middle income countries. Qualitative research has found that a substantial portion of girls’ anxieties about managing their menstruation while at school stems from their fears about boys’ negative reactions [ 1 5 ], impacting well-being and school performance. While many studies aim to understand and improve girls’ menstrual hygiene management (MHM), boys’ attitudes and knowledge of the topic remains under-explored and thus limits their inclusion as agents of positive change.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During menstruation, girls fear teasing by boys and embarrassed if their menstruation is seen. (8) Evidences reveal that adequate menstrual hygiene and management is about availability of sanitary pad, water and soap and separate room for privacy to change and disposal facility. (9) Nonetheless, lack of awareness about the problem at family, school and community level, consideration of menstruation as taboo and consequent teasing and bullying by boys, poor availability of supply including sanitary pad, water, soap, disposal facilities and privacy at school level contributed to girl's school dropout and their poor performance.…”
Section: Introductionmentioning
confidence: 99%